2015
DOI: 10.4103/2229-3485.167096
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of knowledge, attitude, and practice of adverse drug reaction reporting in a tertiary care teaching hospital of Sikkim

Abstract: Aim:Spontaneous voluntary adverse drug reaction (ADR) reporting is paramount to the success of the Pharmacovigilance Programme of India. There has however been minimal and sporadic voluntary reporting of ADR's at the ADR Monitoring Centre (AMC) Gangtok, Sikkim. Knowledge, perception, attitude, and awareness of health professionals are determinants of reporting practices. This questionnaire study aims at evaluating these indicators in the teaching hospital attached to the Medical Institute and find out methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
(18 reference statements)
1
29
0
Order By: Relevance
“…[14][15][16] But the ground reality is, in India, ADR reporting by physician accounted to 64.4%. 17 However, survey in Saudi Arabia showed that 49.3% of the physicians suggested that only serious ADRs should be reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] But the ground reality is, in India, ADR reporting by physician accounted to 64.4%. 17 However, survey in Saudi Arabia showed that 49.3% of the physicians suggested that only serious ADRs should be reported.…”
Section: Discussionmentioning
confidence: 99%
“…11 Physicians from Sikkim (63%) and Indore (66.2%) also considered ADR reporting to be a professional obligation. 15,18 Despite positive attitude from the physicians for the need to report ADRs, in practice there was scarcity of reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This difference, may be because our ADR monitoring center was one this finding is almost similar to previous studies. 16,21 Only 67% of doctors and 52% of nurses believe ADR can sometimes cause death or significant illness to the patients. The reason may be the health care professionals believe that only safe drugs are marketed.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In our study, only 45% participants think that ADR reporting is a professional obligation which is less as compared to other studies. 12,20,21 This is the attitude component which needs to be modified for improving the underreporting of ADR. Good knowledge and attitude remove the misconceptions, obstacles and potential barriers to the activities that we would like to implement thus initiating the practices for reporting.…”
Section: Can't Say 8%mentioning
confidence: 99%